The Performance of Portland Cement Pastes (OPC) Incorporated with Ceramic Sanitary Ware Powder Waste (CSPW) at Ambient Temperature - Darweesh, Hassan; Abu-El-Naga, H (Journal of Sustainable Materials Processing and Management, 2024)
The physical and mechanical performance of Portland cement pastes (OPC) incorporated waste ceramic sanitary ware powder waste (CSPW) at ambient temperature has been investigated. Cement mixes were prepared by replacing the cement with CSPW at proportions of 0, 4, 8, 12, 16 and 20 wt. %. The results showed that the water of consistency and setting times (initial and final) were increased with the gradual addition of CSP, whereas the water absorption and total porosity were decreased, while the bulk density slightly was enhanced but only up to 16 wt. % CSPW. The same trend was displayed with mechanical properties, where the flexural (FS) and compressive strengths (CS) of the cement specimens were also improved and enhanced till 16 wt. %, but then all were decreased with further addition of CSPW. The experimental results indicated that the CSPW has the potential to be successfully recycled in the OPC pastes as a partial replacement merely up to 16 wt. % which had a better performance than the blank at ambient temperature. The FT-IR spectra illustrated that the amount of CSHs was increased, while that of free lime content decreased. This was confirmed by SEM microscopy. Moreover, the recovery of CSPW contributes to both reducing environmental pollution and CO2 emissions.